The Maternity Philosophy of the University Hospital at the Federal University of Santa Catarina, Brazil from the perspective of its users, professionals, and academics: preview note - Isabelle Christine Guerini; Marisa Monticelli; Odalea Maria Brüggemann (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2009)
This study is a quantitative investigation of an exploratory-descriptive nature. Its objective is to evaluate the implementation of the maternity philosophy in a university hospital, under the perspective of its professionals, academics, and users. The data are being collected by self-responding forms, applied among the professionals and with nursing and medical students, as well as through interviews with the pregnant women and their partners. The information obtained is being organized by the EPI INFO program. In the current stage of the research, the data referring to 80 nursing professionals have already been obtained and analyzed, showing that for these subjects the principles which guide maternity care are amply known, with the most valued being related to integral care to its users.